(untitled) (American Journal of Pedagogical and Educational Research, 2024)
The article examines the issues of consideration of cases in arbitration courts, challenging the decision of the arbitration court in state courts. It is concluded that arbitration is an alternative method of dispute resolution, providing the parties with flexibility and expedited consideration of the case. However, the limitation of its competence and the possibility of challenging decisions in the economic court ensure a balance between the independence of arbitration courts and the right of the parties to protect their interests in the state judicial procedure.